The Synergistic Impact of Excessive Alcohol Drinking and Cigarette Smoking upon Prospective Memory - Marshall, Anna-Marie; Heffernan, Thomas; Hamilton, Colin (Frontiers in Psychiatry, 2016)
The independent use of excessive amounts of alcohol or persistent cigarette smoking have been found to have a deleterious impact upon Prospective Memory (PM: remembering future intentions and activities), although to date, the effect of their concurrent use upon PM is yet to be explored. The present study investigated the impact of concurrent use (excessive use of alcohol and cigarette smoking) in comparison to the combined effect of the single use of these substances using a single factorial independent groups design. The Cambridge Prospective Memory Test was administered to 125 adults; an excessive alcohol user group (n = 40), a group of smokers who drink very little alcohol (n = 20), a combined user group (the “Polydrug” group) who drink excessively and smoke cigarettes (n = 40) and a non-drinker/low alcohol consumption control group (n = 25). The main findings revealed that the Polydrug users recalled significantly fewer time-based PM tasks than excessive alcohol users p<.001 and smokers p=.013. Polydrug users (mean = 11.47) also remembered significantly fewer event-based PM tasks than excessive alcohol users p<.001 and smokers p = .013. Most interestingly, Polydrug users exhibited significantly greater impaired time-based PM than the combined effect of single excessive alcohol users and smokers p=.033. However, no difference was observed between Polydrug users and the combined effect of single excessive alcohol users and smokers in event-based PM p=.757. These results provide evidence that concurrent use of these two substances has a synergistic effect in terms of deficits upon time-based PM. The observation that excessive drinking and smoking leads to greater impairments in time-based PM may be of paramount importance, given the key role PM plays in everyday independent living.